Regimes of irradiation by electrons of samples of materials in supercritical water convection loop - Bakai, A.S.; Boriskin, V.N.; Bratchenko, M.I.; Dovbnya, A.N.; Dyuldya, S.V.; Gorenko, Yu.V.; Momot, V.A.; Romanovsky, S.K.; Savchenko, A.N.; Solodovnikov, V.I.; Titov, V.Yu.; Shelepko, S.V.; et al. (Вопросы атомной науки и техники, 2017)
The specially designed in the NSC KIPT Supercritical Water Convection Loop (SCWCL) with an irradiation chamber coupled to an electron accelerator LPE-10 gives an opportunity for corrosion and mechanical tests of materials under electron irradiation. Specimens in water flow are irradiated by the 10 MeV/10 kW electron beam of the LPE-10 linear accelerator at 23…25 MPa and 350…400°C. Presented are the irradiation regime parameters for the 500 hours long work session of the SCWCL.